Sub-project 3: fish trade, processing and marketing (Denmark, 1996)
A major development problem is related to the supply of rural citizens in remote mountainous provinces, who suffer from malnutrition. the growth incom will allow the urban consumers to invest in household storage capacity for frozen fish and meat.
Keywords: Fishery management,Aquaculture; Economic aspects